Education for Sustainable Development (ESD) in Indonesia: A Conceptual Framework - Satrianawati Satrianawati; Wen Heng Fu (Association for Scientific Computing Electrical and Engineering(ASCEE), 2019)
Some schools in certain regions of Indonesia are currently really dangerous because they are in the ring area of the fire. In the region, there are also schools located in disaster-prone areas. This research aims to describe modern education for sustainable development by building the online school as disaster solution in the modern era. This research is descriptive qualitative research using a social history approach. The design research method was carried out in four phases: data collection, data display, conclusions, and data condensation. The result of this research is the government should be building an online school as a disaster solution for the generation in the modern era to education for sustainable development.